Disease interception with interleukin-17 inhibition in high-risk psoriasis patients with subclinical joint inflammation - Data from the prospective IVEPSA study - Kampylafka, Eleni; Simon, David; D'Oliveira, Isabelle; Linz, Christina; Lerchen, Veronika; Englbrecht, Matthias; Rech, Jürgen; Kleyer, Arnd; Sticherling, Michael; Schett, Georg; Hueber, Axel (Arthritis Research & Therapy, 2019)
Background: A specific subset of psoriasis patients is characterized by subclinical inflammatory changes. These patients frequently present with arthralgia and have a higher risk to develop psoriatic arthritis (PsA). We hypothesized that IL-17A inhibition in this subset of patients can intercept the link between skin and joint disease and resolves pain and inflammatory changes. Methods: Psoriasis, but no PsA, patients were included in the open prospective exploratory Interception in very early PsA (IVEPSA) study. Patients had to have nail or scalp involvement or a high psoriasis area severity index (PASI) (> 6) as well as inflammatory or erosive changes in MRI or CT. Patients received treatment with the anti-interleukin (IL)-17A antibody secukinumab over 24 weeks. Clinical assessments of skin and joint disease were done at baseline and after 12 and 24 weeks, MRI and CT at baseline and after 24 weeks. Results: Twenty patients were included, 85% of them reporting arthralgia and 40% had tender joints at the examination. Eighty-three percent had at least one inflammatory lesion in the MRI, most of them synovitis/enthesitis. Skin disease (PASI: p < 0.002; BSA: p < 0.003) and arthralgia (VAS pain: p < 0.003) significantly improved after 24 weeks. Total PsAMRIS (p = 0.005) and synovitis subscore (p = 0.008) also significantly improved. Erosions and enthesiophytes did not progress, while bone mass in the distal radius significantly (p = 0.020) increased after 24 weeks. Conclusions: These data suggest that very early disease interception in PsA is possible leading to a comprehensive decline in skin symptoms, pain, and subclinical inflammation. IVEPSA therefore provides rationale for future early interventions with the concept to prevent the onset of PsA in high-risk individuals. Trial registration: Trial registry name PSARTROS; trial registry number: NCT02483234; June 26, 2015.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Interleukin-17; Magnetic resonance imaging; Psoriasis; Psoriatic arthritis